The negative aspects of the influence of the Dari language by the Arabic language - Nahzat, Abdulrahman (Journal of Humanities & Social Sciences, 2020)
The impact and influence on languages is natural, as there is no civilized language in this globe except that it affects or is affected by other languages, However when the issue of the influence of the Dari language is raised in the Arabic language, it often comes to mind that positive aspects and consequences of this influence are affected., There is no doubt that this impact has many positive aspects. Moreover, it also has negative aspects, which made me prepare and write this humble article.The influence of the Dari language at the end of the day leads to a severe rapprochement between the two languages, which makes some speakers of the Arabic language who are familiar with the Dari language, and I have mentioned these mistakes and outlined them in the following points:1.They make mistakes because they utter abandoned or dead Arabic words and phrases by claiming that they are living words or phrases that prevail today in the Arabic language.2.They are making mistakes because they did not use the Arabic words that have origins and are used and prevalent in Arabic because they think that the Arabic words and words equivalent to them are used today in Arabic, and the truth is otherwise.3.They are making mistakes because they do not use authentic Arab words and phrases brazen and prevalent today in Arabic because they think that they are pure words and phrases.4.Their mistakes because they did not use the daring Arabic words used in Arabic, because they claim that Arabic has Arabic slogans used in that and the truth is the opposite of this.• Their mistakes in not understanding the meanings of some common words between the two languages, which are written with the same letters, vowels, and dwellings in both of them.
Keywords: influence and vulnerability; negative aspects; Arabized words; abandoned words; strange words and dominant words